Phenotypic and Genotypic Characterisation of Extended Spectrum Beta-Lactamases (Esbls) and Ampc Beta Lact Amases among Klebsiellapneumoniae - REMYA. P.A,; SHANTHI.M,; UMA SEKAR, (International Journal of Pharma and Bio Sciences, 2018)
Klebsiellapneumoniae, is an important pathogen causing community acquired and nosocomial infections. Production of AmpC and ESBLs confer multidrug resistance in them. The spread of ESBLs and AmpC beta- lactamase producing Klebsiellapneumoniae is a major health concern globally. Most of the clinical laboratories have difficulty in detecting ESBLs and AmpCs, because of their co-existence and their ability to mask each other. Failure to detect these enzymes can result in their rapid spread and therapeutic failure. This study was done to detect the presence of ESBLs and AmpC by phenotypic and molecular methods in clinical isolates of Klebsiellapneumoniae. A total of 370 isolates of Klebsiellapneumoniae, isolated from various clinical samples over a period of one year was included in this study. Antibiotic susceptibility testing for various classes of antimicrobials was done as per CLSI 2015 guidelines. Presence of ESBLs (TEM,SHV,CTX-M) and plasmid mediated AmpCs (MOX, CIT, DHA, ACC, EBC, FOX) in clinical isolates were detected by both phenotypic and genotypic methods. Among 370 isolates 58.91% were resistant to any one of the third generation cephalosporins.Phenotypic test detected 37.02 % isolates as ESBL producers. Co-existence of all three genes (TEM,SHV,CTX-M) were seen in 47.29% in this study. In 79 isolates, by PCR ESBL genes (one or more) were detected though the phenotypic test was negative in them. Cefoxitin resistance was exhibited by 118 isolates of which 34 harboured AmpC genes. The most prevalent AmpC gene in this study was DHA (n=29) followed by EBC (n=3) and CIT (n=2). Phenotypic test for ESBLs and AmpC can give false positive or negative result. Detection of the resistance mechanism by molecular methods will help to prevent therapeutic failure and the spread of multi drug resistant Klebsiellapneumoniae.